Turystyka w rozwoju regionu (na przykładzie regionu podlaskiego) - Długokęcka, Marzena (Tourism in the Development of a Region (on the Example of the Podlaski Region), 2005)
Tourism including agritourism is becoming popular and dynamically developing area of economy. Natural resources, architecture, landscape advantages, human resources, right country infrastructure, traditions connected with a region are these factors which encourage tourists to take a rest in Podlaski region.Podlaski region has rich touristic potential. According to people who run analysed activities, this form of holiday popularity depends not only on inhabitants but also on local governments.Touristic economy fulfils a vital role in rural areas activation in the analysed region. It's recognised as one of key factors of development and a source of opportunities for other branches and services.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 149-154